Les fonctions du rituel scolaire selon différentes sciences humaines et sociales - Myriam Bertrand; Maryvonne Merri (Recherches en Éducation)
This article offers a multidisciplinary review of the functions of school rituals. Firstly, three categories of functions are analyzed: social functions, learning functions, and language functions. In this research, sociological and anthropological references are articulated with Vygotsky’s cultural psychology and didactics, revealing the potential functional richness of school rituals. Secondly, in order to analyze this multi-functionality and its implementation, we propose, following Garcion-Vautor, to mobilize the structural approach developed by Rivière.